The nursing care to the elderly people: a reflexion according to the transcultural theory of Leiniger - Janei Rabello de Souza; Ivete Palmira Sanson Zagonel; Mariluci Alves Maftum (Rev Rene)
This article aims to reflect on elderly nursing care in the light of Madeleine Leininger’s Transcultural Theory as well as to suggest a care model. The theory values the importance of cultural factors over human beings, and that their absence in nursing care planning will bring about unrelated actions to individual’s cultural reality. Caring elders in an incongruent way, regarding their patterns and beliefs, may give rise to cultural clashes, frustration, stress and moral and ethical concerns. We point out nurses’ need to make use of that theory in order to provide elderly people with care permeated by valuing cultural diversities.